Extreme X‐ray beam compression for a high‐resolution table‐top grazing‐incidence small‐angle X‐ray scattering setup. (25th October 2013) - Jergel, Matej; Šiffalovič, Peter; Végsö, Karol; Majková, Eva; Korytár, Dušan; Zápražný, Zdenko; Perlich, Jan; Ziberi, Bashkim; Cornejo, Marina; Vagovic, Patrik
<x xml:space="preserve">Abstract</x> The application of V‐shaped channel‐cut GeSi(220) and Ge(220) monochromators for one‐dimensional extreme X‐ray beam compression was tested on a table‐top setup for grazing‐incidence small‐angle X‐ray scattering (GISAXS) with a microfocus source. A lattice constant gradient and different asymmetry angles of the diffractors were employed to enhance the compression factor to 21 and 15, respectively. It was demonstrated that the output beam parameters in terms of the size, divergence, photon flux and spectral bandwidth surpass those of the slit collimators used traditionally in GISAXS. A beam size far below 100 µm allows a high‐resolution spatial GISAXS mapping, while the reciprocal space resolution of ∼500 nm approaches the level of synchrotron measurements and allows a fast one‐shot detection of high‐resolution GISAXS patterns. An oversampling shifts the detection limit up to ∼1 µm. The very short design of the compact high‐resolution table‐top GISAXS setup is another advantage of the extreme beam compression. Benefits of V‐shaped monochromators for medium‐resolution X‐ray diffraction experiments as a bonus application are demonstrated by a comparison with parallel channel‐cut monochromators combined with a slit.